Cinquant’anni di giurisprudenza e di psicoterapia - Dall'Olio, Francesco (Il sogno della farfalla, 2012)
The article analyzes the sentence passed by the Italian Supreme Court on the 11th April 2011 from the judicial point of view, demonstrating how its “historic” nature is contained in the continuity of the principle it affirmed in previous jurisdictions whereby psychotherapy constitutes a medical act. In particular it focuses on two other judicial pronouncements made by the Supreme Court in 1970 and 1972, which alongside the present ones are discussed in relation to developments in psychiatric thinking.